Optimal Institution for Operational Supervision of Government Development Projects in Light of Economic Analysis of Law and Legal Requirements - Mohamadhossein Sadeghi; Vali Rostami (پژوهش‌های برنامه و توسعه)
Efficiency and Effectiveness of the government are integral components of good governance, and its realization in government investment in development projects also appears in legal rules, so it can be realized by improving the legal rules governing such projects. Among the numerous legal rules of project controlling, it can be found the one that emphasizes the efficiency and effectiveness of the projects more than other types. Operational supervision is controlling the efficiency and effectiveness of development projects, and in the Iranian legal system, according to Article 126 of the constitution, it is one of the responsibilities of the president who exercises it through his deputy. On the other hand, in many countries, such as the United States, operational supervision of the controlling pertains to the Audit Court, which in turn is overseen by parliament. The question is whether it is possible to change the controlling Institution from "Plan and Budget Organization" to the "Supreme Audit Court"? Article 55 of the Iran constitution takes Audit Court only in charge of traditional controlling, so it seems that considering the current constitution, it is not possible to change the competent institution in charge of operational supervision.